Appraising offsets as a tool for integrated environmental planning and management. (20th March 2018) - Lodhia, Sumit; Martin, Nigel; Rice, John
Abstract: The steady growth in major development projects suggests that firms will increasingly need to respond to more stringent environmental determinations and project approvals. Accordingly, this article positions offsets as a mechanism for integrated environmental planning and management in response to development impacts. The study uses a stakeholder analysis methodology to identify and explicate the environmental planning and management practices that can be delivered by offsets, while demonstrating how firms and governments may use offsets as a tool to plan and manage environmental conservation and protection. However, despite our positive expectations, the research found that the current framework of offsets rules, regulations and supporting infrastructure requires changes if effective planning and management of the environment is to be facilitated through the offsets mechanism. Highlights: Offsets are often used to reduce environmental impacts. Offsets can used for environmental planning and management. Stakeholder analysis was undertaken to determine management practices that can be enabled through offsets. Findings suggest that current framework for offsets needs to change to enable integrated planning and management.